2011
DOI: 10.1097/pai.0b013e3181f7b30f
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Presentation of Hairy Cell Leukemia and Metastatic Signet Ring Carcinoma of the Stomach Diagnosed by Bone Marrow Biopsy

Abstract: Hairy cell leukemia (HCL) is a rare chronic B-cell disorder with an increased risk of second tumors. The relative risk of second cancers reported in various series of HCL patients ranged from 0.95 to 4.33, but simultaneous presentation of HCL and other epithelial malignancies is very rare. To our knowledge, we present the first case of the coexistence of signet ring carcinoma of the stomach and HCL. We report a case of the simultaneous presentation of HCL and metastasis of the primary signet ring cell carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The relative risk of second cancers reported in various series of HCL patients ranged from 0.95 to 4.33, but simultaneous presentation of HCL and solid malignancies is very rare. Simultaneous presentation of HCL and solid malignancy is exceptional and only a few cases have been described [12][13][14] . It has been described synchronous occurrence of HCL with neuroendocrine colon carcinoma, HIV-negative Kaposi's sarcoma and signet ring carcinoma of the stomach [12][13][14] .…”
Section: Discussionmentioning
confidence: 97%
“…The relative risk of second cancers reported in various series of HCL patients ranged from 0.95 to 4.33, but simultaneous presentation of HCL and solid malignancies is very rare. Simultaneous presentation of HCL and solid malignancy is exceptional and only a few cases have been described [12][13][14] . It has been described synchronous occurrence of HCL with neuroendocrine colon carcinoma, HIV-negative Kaposi's sarcoma and signet ring carcinoma of the stomach [12][13][14] .…”
Section: Discussionmentioning
confidence: 97%
“…19 Subsequently, other studies in HCL patients reported ranges of relative risk of second carcinogenesis of 0.95–4.33. 20 In 1997, a study conducted at the M.D. Anderson Cancer Registry involving 350 patients with HCL described 26 cases (7.4%) of second cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[1–24] However, it should be noted that hematolymphoid neoplasms can also present with signet-ring cell morphology which may lead to diagnostic pitfalls. [24–28] Here, we present a very unusual case of a 67-year-old female with invasive lobular breast carcinoma, confirmed by breast biopsy and histopathologic examination. One year after surgery with combined chemotherapy and radiotherapy, the patient was noted to be thrombocytopenic.…”
Section: Introductionmentioning
confidence: 95%